Bahasa Inggris - Desmalinda (JOURNAL OF GOVERNMENT SCIENCE, 2026)
This study examines the phenomenon of the anonymous social media account Fufufafa as a distinctive case within Indonesian digital democracy. The controversy escalated rapidly because it was associated with the Vice President-Elect, marking the first instance in which an anonymous account targeted high-level political figures and triggered nationwide debate. Drone Emprit recorded over 112,000 interactions across platform X between 28 August and 18 September 2024. Using a qualitative approach supported by Social Media Network Analysis (SMNA), this study maps discourse networks, identifies influential actors, and analyzes dominant narratives. The findings show that civic participation was largely driven by anger and surprise, expressed through hashtags, retweets, and public commentary. These reflected moral dissatisfaction related to nepotism, ethical misconduct, and political integrity, demonstrating that cultural norms strongly shaped public reaction. Shared cultural norms regarding honesty, integrity, and accountability connected citizens, enabled collective moral judgments, and encouraged public scrutiny of political elites, thereby functioning as a form of digital social capital. While this norm-based participation expanded civic expression and decentralized political engagement, it also produced echo chambers that constrained inclusive deliberation. This study concludes that strengthening Indonesia’s digital democracy requires not only regulatory and literacy efforts but also the cultivation of cultural norms and ethical digital cultures that ensure the online sphere remains a deliberative arena for substantive democracy.